On the importance of neutral composition and temperature measurements in the 100–200 km altitude region - Jones, McArthur; Emmert, John T.; Gan, Quan; Yue, Jia (Frontiers in Astronomy and Space Sciences, 2022)
Currently, thermospheric species densities and temperatures between ~100-200 km are not known to the accuracy needed to fully characterize how the thermosphere transitions from a well-mixed atmosphere to a diffusively separated atmosphere with zero temperature gradient. This greatly inhibits scientific discovery attainable from either models or observations in this region, especially the understanding of mechanisms that drive thermosphere and ionospheric variability from space weather to climatological time scales. The purpose of this paper is to highlight the importance and critical need for new, global, height-resolved neutral composition (O,O2,N2) and temperature measurements in the new ignorosphere: the 100-200 km region of the thermosphere. We conclude with observation recommendations and requirements for new comprehensive composition and temperature measurements in the 100-200 km altitude region that would lead to significant advances in thermosphere-ionosphere science, space weather, and space climate.